Ginkgo biloba extract EGb761 mitigates ischemic stroke via metabolic pathway modulation - Xiaoyao Liu; Yuan Tian; Wenhui Xu; Yuxi Wang; Zhen Liu; Yuncheng Ma; Weiling Wang; Jian Gao; Ting Wang (Journal of Traditional Chinese Medical Sciences)
Objective: To confirm the therapeutic efficacy of the ginkgo biloba extract EGb761 on ischemic stroke and elucidate its underlying mechanism. Methods: Male Sprague-Dawley rats were divided into three groups: sham, model, and EGb761 (ginkgo biloba extract). Ischemic stroke was then simulated in rats via embolic middle cerebral artery occlusion surgery, with the extract administered half an hour before surgery. Neurological deficit scores, infarct volume, cerebral edema rate, and inflammatory factors served as the primary metrics for drug efficacy. Serum metabolites were analyzed using 1H-nuclear magnetic resonance to elucidate the operative mechanism. Results: Treatment with the ginkgo biloba extract EGb761 significantly ameliorated the neurological deficit scores (P = .0343), diminished the cerebral infarct volume (P = .0001) and cerebral edema rate (P = .0030), and alleviated neuroinflammation (all P < .05) in middle cerebral artery occlusion rats. In addition, it significantly altered the contents of various metabolites, such as 2-hydroxybutyrate, isoleucine, isopropanol, isobutyric acid, N6-acetyllysine, glutamate, glutamine, methionine, and N,N-dimethylglycine (all P < .05). Enrichment analysis of the differential metabolites indicated that EGb761 may be involved in the regulation of amino acid metabolism, betaine metabolism, glucose-alanine cycle, Warburg effect, and urea cycle. Conclusion: The ginkgo biloba extract EGb761 demonstrates anti-ischemic stroke effect on ischemic stroke model rats by regulating amino acids and amino acid derivatives, such as isoleucine, N6-acetyllysine, glutamate, methionine, and N,N-dimethylglycine.